Constructions for new orthogonal arrays based on large sets of orthogonal arrays - Chen, Guangzhou; Niu, Xiaodong (Designs, codes, and cryptography, 2023)
Orthogonal array is one of the important research subjects in combinatorial design theory and experimental design theory, and it is widely applied to statistics, computer science, coding theory and cryptography. There are many constructions and results for orthogonal array of strength 2, however the results on orthogonal array of strength t ≥ 3 are rare. In this paper, we first present two new effective constructions for orthogonal arrays of strength t ≥ 3 based on large sets of orthogonal arrays. Second, many infinite families of large sets of orthogonal arrays are obtained and then some new series of orthogonal array of strength t ≥ 3 are produced.